2014
DOI: 10.1080/13102818.2014.967746
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofHuman parvovirus B19(HPVB19) in serum samples from fever-rash ill individuals during the rubella outbreak (2005) in Bulgaria

Abstract: The present study aimed to determine the involvement of the parvovirus B19 (HPVB19) as an etiological agent in individuals with fever-rash infections but not infected with rubella during the rubella outbreak (2005) in Bulgaria. A total of 194 serum samples with negative results for measles and rubella-specific IgM antibodies were tested in the National Reference Laboratory. The individuals aged 5–52 years (mean age 17.2 ± 10.15) were divided into four age groups: 5–14; 15–24; 25–34; and 35+ years old. Serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Indeed, according to data from the Ministry of Public Health, several outbreaks of measles-like rashes have occurred over the last 5 years in Katanga. As B19V IgM antibodies and DNA were found in sera from all provinces of DRC, it can be confirmed that B19V has spread countrywide, and this supports the hypothesis that B19V has a worldwide distribution ( Rezaei et al, 2016 , Zhang et al, 2016 , Toshev et al, 2014 , Tolfvenstam et al, 2000 , Schwarz et al, 1989 ).…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, according to data from the Ministry of Public Health, several outbreaks of measles-like rashes have occurred over the last 5 years in Katanga. As B19V IgM antibodies and DNA were found in sera from all provinces of DRC, it can be confirmed that B19V has spread countrywide, and this supports the hypothesis that B19V has a worldwide distribution ( Rezaei et al, 2016 , Zhang et al, 2016 , Toshev et al, 2014 , Tolfvenstam et al, 2000 , Schwarz et al, 1989 ).…”
Section: Discussionsupporting
confidence: 71%
“…While the lowest yearly proportions of B19V IgM positives in the present study were detected during the 2009 to 2010 measles outbreak (6% and 13%), a high proportion of more than 47% was found towards the end of the 2005 to 2006 rubella outbreak. A recently published study based on a somewhat different patient cohort and only 194 samples collected early during the 2005 to 2006 rubella outbreak, found an even higher rate of IgM positivity of 48.97% [5]. The more similar clinical presentation of rubella and B19V infections, but also the increased B19V incidence reported from elsewhere in Europe in 2005 and 2006 [3,16] may explain the apparent positivity rate difference during the measles and rubella outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In Bulgaria, as well as in most other countries, this infection is not a notifiable disease. However, the clinical presentation of B19V infection is sometimes mistakenly diagnosed as rubella or measles [3][4][5], which are both notifiable diseases in Bulgaria. An accurate diagnosis of fever/rash illness is necessary for case management and public health control activities [6], in particular in the context of the World Health Organization's goal to eliminate measles and rubella in the European Region [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…B19V is frequently reported in measles and rubella negative cases and in our study more than 10% of the patients were B19V IgM antibody positive without any seasonal or geographic pattern. The percentage of B19V positives among rash and fever patients varies widely (eg, 2.40% in a study from Brazil; 48.97% among measles and rubella negative patients from Bulgaria and depends among other factors on geographical region, measles and rubella control status and age groups tested. In the present study, positive cases were found in all age groups, but especially among children between 5 and 9 years and in adults above the age of 19 years.…”
Section: Introductionmentioning
confidence: 99%